Disclosures of Social Value Creation and Managing Legitimacy: A Case Study of Three Global Social Enterprises. Issue 3 (20th January 2017) - Islam, Muhammad Azizul
Abstract : This study seeks to fill the gap in the existing literature by examining how and whether disclosure of social value creation becomes a part of the legitimation strategies of social enterprises. In particular, using Suchman's (1995) moral dimension of legitimacy theory, this study sets out whether and how disclosures by three global social organisations – Grameen Bank, Charity Water and the Bill & Melinda Gates Foundation – conform to the expectations of the broader community. The study finds that there is an apparent disconnection between disclosure and action by social enterprises. With reference to a few incidents, social enterprises use disclosure as a part of their managerial efforts, rather than to create moral legitimacy. The notion of apparent disconnection between disclosure and real action by social enterprises is evident. The notion is consistent with extant disclosure literature capturing the motivations for the disclosure practices of corporations. The findings of this paper suggest that when an organisation (whether it is a corporation or a social enterprise) faces a legitimacy crisis, it appears to disclose good news rather than bad news, which calls into question organisational moral legitimacy. Abstract : This study examines disclosures of social value creation by three global social enterprises, Grameen Bank, Charity Water, and the Bill and Melinda Gates Foundation. The study finds that there is an apparent disconnection between disclosure and actions by social enterprises.